The Thoughts of KH. Bisri Mustofa’s Moral Education and its Relevance with Development of Character Building - M Sofyan Alnashr; Amin Suroso (The Institute of Research and Service Community IPMAFA Pati, 2020)
This study aims to describe the thoughts of K.H. Bisri Mustofa’s moral education in the books of Mitro Sejati and Ngudi Susilo and its relevance with the development of character building in Indonesia. To describe the concept of moral education in the aforementiod books, content analysis was used to grasp the main messages of the books. The finding showed that the thoughts of K.H. Bisri Mustofa’s moral education were relevant with the development of character building proclaimed by the government. The relevancyecould be found in the foundational thinking about moral education contended by K.H. Bisri Mustofa and character education in Indonesia, encompassing the importance of humanism in social interaction, moral degradation among adolescents, and the erosion of Eastern culture by Western culture. Relevance was also found in the five main character values ​​that were prioritized in the implementation of the development of character building in which each value is relevant to KH. Bisri Mustofa. These values ​​include religious, integrity, nationalist, independent, and mutual cooperation.